Pengaruh Insentif Pajak Dalam PMK No. 82 Tahun 2021, Pengetahuan Wajib Pajak, Pelayanan Pajak, dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak UMKM Di Kota Denpasar - Ketut Budi Artawan; Sang Ayu Putu Arie Indraswarawati; I Wayan Budi Satriya (UNHI Press, 2023)
This study aims to analyze the effect of tax taxes in PMK no 82 of 2021, taxpayer knowledge, and tax taxes on MSME taxpayer compliance in Denpasar City. This research was conducted in Denpasar City. The object of the research is taxpayer compliance obtained by taxes, taxpayer knowledge, tax services and taxation taxes. This research uses the population of MSMEs in Denpasar City which are recorded at the East and West Denpasar KPP as many as 224,913 businesses. The results of the analysis of the applicable sample for the population. So, the sample used must be able to represent the population. The method of entering the sample uses purposive sampling, which is to determine the sample based on certain criteria. the sample size used is the slovin formula with the number of samples in this study rounded up to 100 people who are obliged to determine the MSME tax. The technique for taking samples is incidental sampling. The distribution of the questionnaires was carried out using a google form considering the pandemic situation, which was analyzed by linear regression. The results showed that PMK No.82 Year 2021 tax incentives, taxpayer knowledge, and tax taxes had a positive and significant impact on MSME taxpayer compliance in Denpasar City.